Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini) - Martinez, Leonel; Galvis, William (Zootaxa, 2017)
Three new jumping spiders of the genus Hypaeus Simon, 1900 are described and illustrated from Colombia, two of which are sympatric: H. arhuaco sp. nov. and H. proszynskii sp. nov., from Sierra Nevada de Santa Marta, Magdalena department. The third species, H. varzea sp. nov., is described from a várzea forest in the Amazonas department. The new species are diagnosed based on sexual characters, such as the retrolateral tibial apophysis, retroventral tibial apophysis and the embolus (male palp), and length and disposition of the copulatory ducts and digitiform glands (epigyne).